Issues and Challenges of Adoption of IFRS for SMEs in Malaysia - Vicky Vendy; Diarany Sucahyati (Nusantara Science and Technology Proceedings, 2021)
The purpose of this research is to look into issues and challenges associated with the adoption of International Financial Reporting Standards for Small and Medium Enterprises (IFRS for SMEs) or so-called MPERS (Malaysian Private Entity Reporting System). Using keywords like "IFRS for SMEs," "MPERS in Malaysia," and so on, this study examines existing literature in the form of articles in the Emerald database, as well as press releases and publications published by the Malaysian Institute of Accountants (MIA). The MPERS version of IFRS is a shortened version of the complete IFRS. It reduces the substance of the whole IFRS by about 85%. Certain topics are excluded because they are not normally relevant to SMEs. SMEs, on the other hand, still consider IFRS for SMEs to be excessively complicated. MPERS is a performance-based standard, not a cost-based one. Almost everything must be of reasonable value. As a result, businesses owning investment properties or biological assets will have to pay extra for the valuation of these assets at fair value. For preparers, there are two major obstacles to overcome. Constant changes in standards, as well as a scarcity of skilled accountants, are also issues. Some data suggests that the decision usefulness model is inappropriate for smaller businesses. SMEs have a small number of account users, lack accounting competence to deal with complexity, and are managed by their owners. Furthermore, for SMEs, a reporting approach focused on stewardship and employing simplified historical cost accounting would be more appropriate.